Efficient Synthesis of Thiolactoside Glycoclusters by Ruthenium-Catalyzed Cycloaddition Reaction of Disubstituted Alkynes on Carbohydrate Scaffolds - Cagnoni, Alejandro (2013)
Lectin-carbohydrate interactions are responsible for several cellular processes involved in the immune system and the development of certain types of cancer. To further understanding of the cellular responses triggered by these interactions, complex carbohydrates are designed and prepared. Here, we describe the synthesis of a family of multivalent glycoclusters based on carbohydrate cores bearing thiolactosides or thiogalactosides as recognition elements with structural valencies ranging from 2 to 8. The synthetic strategy involves a key ruthenium-catalyzed cycloaddition reaction between symmetric disubstituted alkynes bearing two thiosugar units and azide-containing carbohydrate scaffolds. This methodology afforded high-valency glycoconjugates in good to excellent yields. Binding affinities of the synthetic β- thiolactosides for peanut lectin were measured by isothermal titration calorimetry. These titrations revealed micromolar affinities as well as a multivalent effect. A tetravalent glycoconjugate based on a trehalose scaffold displayed the highest binding affinity.